Stem Cells in the Periodontium—Anatomically Related Yet Physiologically Diverse - Ponnaiyan, Deepa; Rughwani, Roshan R.; Victor, Dhayanand John; Shetty, Ganesh (European Journal of Dentistry, 2022)
Periodontitis is a complex chronic disease discernible by the deterioration of periodontal tissue. The goal of periodontal therapy is to achieve complete tissue regeneration, and one of the most promising treatment options is to harness the regenerative potential of stem cells available within the periodontal complex. Periodontal ligament stem cells, gingival mesenchymal stem cells, oral periosteal stem cells, and dental follicle stem cells have structural similarities, but their immunological responses and features differ. The qualities of diverse periodontal stem cells, their immune-modulatory effects, and variances in their phenotypes and characteristics will be discussed in this review. Although there is evidence on each stem cell population in the periodontium, understanding the differences in markers expressed, the various research conducted so far on their regenerative potential, will help in understanding which stem cell population will be a better candidate for tissue engineering. The possibility of selecting the most amenable stem cell population for optimal periodontal regeneration and the development and current application of superior tissue engineering treatment options such as autologous transplantation, three-dimensional bioengineered scaffolds, dental stem cell-derived extracellular vesicles will be explored.
Keywords: 3D-bioprinting; exosomes; immune phenotype; periodontal regeneration; periodontal stem cells; regenerative medicine; stem cells; tissue engineering